Winter's law and the loss of stops before obstruents in Proto-Slavic - Matasović, Ranko (Array, 2011)
The paper shows how a re-formulation of Winter's law helps us clarify a number of Slavic etymons which have not been adequately treated in etymological dictionaries so far. In all of the cases discussed in the paper it is assumed that a voiced stop, responsible for Winter's lengthening, was lost before another obstruent in the closed syllable.